Linoleic acid isomerization ability of Lactobacillus spp. isolated from Vietnamese human intestinal origins - Xuan Thach, Tran; Thi Thu, Ha; Thi Hien, Vu; The Hung, Hoang; Thi Hoa, Nguyen; Thu Hong, Le Thi; Ngoc Anh, Luu Dam; Van Huong, Bui; Lan Anh, La Thi; Van Quyen, Dong; et al. (Vietnam Journal of Biotechnology, 2020)
Conjugated linoleic acid (CLA) have been shown to exert numerous health benefits, including anti-carcinogenic, anti-atherogenic, anti-diabetic, antiobesity, cholesterol reducing, antioxidant, anti-microbial, immune system modulator and growth-stimulating properties. In human, CLA is produced from Linoleic acid (LA) by gut bacteria. In this study, nineteen Lactobacillus (Lac.) strains isolated from human feces were studied to determine their ability to metabolize LA. The bacteria were grown in the liquid form of anaerobic MRS medium supplemented with 0.5 mg/mL LA. The linoleate isomerase activity in bacteria grown on MRS medium was determined by Gas chromatograpy. The results indicated that 4 out of 19 strains, including strains Lac.02, Lac.05, Lac.14 and Lac.16 are capable of producing about 40-50 μg/mL CLA from LA. Among them, the highest ability to produce CLA from LA is Lac.02 strain. In the production of CLA from LA, enzymes involved in this metabolism in Lactobacillus act as catalysts of hydration/dehydration (CLA-HY), oxidation of hydroxy groups/reduction of oxo groups (CLA-DH), migration of carbon-carbon double bonds (CLA-DC), and saturation of carbon-carbon double bonds (CLA-ER). The cla-dh, cla-dc, cla-hy and cla-er genes that encode enzymes CLA-DH, CLA-DC, and CLA-ER had been found in all Lac.02, Lac.05, Lac.14 and Lac.16 strains. Gas chromatography traces indicated that these strains produced the same compounds, which was subsequently identified as cis-9, trans-11, and trans-10, cis-12 CLA. In the next study, we will optimize the conditions such as substrate concentrations, pH values, temperature and culture time of each strain to obtain the best rerults.